Modeling interdisciplinary interactions among physics, mathematics and computer science - Rima Hazra; Mayank Singh; Pawan Goyal; Bibhas Adhikari; Animesh Mukherjee (Journal of Physics: Complexity)
Interdisciplinarity has over the recent years have gained tremendous importance and has become one of the key ways of doing cutting edge research. In this paper we attempt to model the citation flow across three different fields—physics (PHY), mathematics (MA) and computer science (CS). For instance, is there a specific pattern in which these fields cite one another? We carry out experiments on a dataset comprising more than 1.2 million articles taken from these three fields. We quantify the citation interactions among these three fields through temporal bucket signatures . We present numerical models based on variants of the recently proposed relay-linking framework to explain the citation dynamics across the three disciplines. These models make a modest attempt to unfold the underlying principles of how citation links could have been formed across the three fields over time.